Application of the accelerated rehabilitationprotocol (ERAS) in the perioperative period from the position of an anesthesiologist - S. N. Gritsenko; O. S. Lashkul (Сучасні медичні технології)
Introduction. Application of laparoscopic techniques corresponds to the principles of the ERAS maximally.